Application of the Single Moving Average, Weighted Moving Average and Exponential Smoothing Methods For Forecasting Demand At Boy Delivery - Muhammad Asyrof Hidayatullah Alex; Nur Rahmawati (Tibuana, 2023)
Boy Delivery is a delivery service in the city of Lamongan which has been operating for about 4 years. Boy Delivery has an average of 12,000 demand per month. However, the high demand was not accompanied by good demand management, Boy Delivery often piled up and even rejected a number of demand due to the unavailability of drivers at that time, this was due to an incorrect prediction of demand. Therefore this research was conducted to help forecast future demand using the Single Moving Average, Weighted Moving Average, and Exponential Smoothing methods. Of the three methods, the Single Exponential Smoothing method was obtained as the best method with the most accurate results with a smaller error of 5.481%.